Age-dependent interaction between serum zinc and triglyceride-glucose index among American adults: National Health and Nutrition Examination Survey - Lai, Jun; Li, Xin-Qing; Zheng, Yinglin; Liu, Zongyan; Wu, Qiquan; Cao, Yongxiao (Frontiers in Nutrition, 2025)
IntroductionZinc plays a crucial role in glucose metabolism. The association between serum zinc and insulin resistance has recently been investigated as well, but the findings are inconsistent. The triglyceride-glucose index (TyG) is frequently utilized in epidemiological research to assess insulin resistance. The association between serum zinc levels and TyG has not yet been explored. Therefore, we designed this cross-sectional study to assess the relationship between serum zinc and TyG in adults using data from the National Health and Nutrition Examination Survey (NHANES).MethodsA cross-sectional analysis was performed on 1,610 adults aged ≥20 years who participated in the National Health and Nutrition Examination Survey (NHANES) 2011–2016. The participants were stratified by age, and the differences in log-transformed serum zinc quartiles and TyG were further evaluated in age groups <60 years and ≥60 years using multivariable linear regression with an interaction test. Additionally, a restricted cubic spline (RCS) model was employed to examine the dose-response relationships between log-transformed serum zinc and TyG.ResultsIn this cross-sectional study, a significant interaction was observed between log-transformed serum zinc and TyG in individuals aged <60 years and those aged ≥60 years when log-transformed serum zinc was transformed into a categorical variable (P-value for the likelihood ratio test for the interaction was P = 0.017). Additionally, in the fully adjusted analyses, the association between log-transformed serum zinc and TyG in the age <60 years group demonstrated a J-shaped nonlinear pattern (P for nonlinearity = 0.014), with an inflection point at ~1.94 μg/dL. While in the age ≥60 years group, it exhibited an inverted-L shaped nonlinear pattern (P for nonlinearity < 0.001***).ConclusionThere is a significant relationship between log-transformed serum zinc and TyG in adults in the United States, with age potentially influencing this association. Further prospective studies are needed to offer additional evidence and insights into these findings.